Examining Agricultural Communities' Views on Provisioning Ecosystem Services from the Batang Toru Forest - Hamid Arrum Harahap; Yonariza; Endrizal Ridwan; Yuerlita (Fakultas Kehutanan UNIPA, 2023)
Our study investigates the significance of ecosystem services for agricultural production and rural livelihoods, specifically focusing on the Batang Toru forest in North Sumatera. Through household surveys and descriptive analysis, we gather data on farmers' preferences for specific ecosystem services and examine their benefits for agriculture. Our findings highlight the crucial role of provisioning services, including food crops and non-timber forest products, in sustaining farmers' livelihoods within the study area. We also underscore the prevalence of agroforestry practices and stress the necessity for targeted interventions to enhance sustainability and productivity. Furthermore, our study provides valuable insights into the intricate relationship between farmers' perceptions of ecosystem services and various influencing factors in the Batang Toru forest context. Positive correlations are observed between land size, frequency of interactions with forested areas, benzoin farmers, and farmers engaged in other non-timber forest products, signifying the importance of these factors in shaping farmers' recognition of the forest's contributions. By understanding these factors, policymakers and practitioners can develop effective strategies to promote the sustainable management and utilization of ecosystem services in the Batang Toru forest region, benefiting both farmers and the surrounding environment.